PENGARUH KEPEMILIKAN INSTITUSIONAL, KARAKTER EKSEKUTIF DAN KONEKSI POLITIK TERHADAP TAX AVOIDANCE - Laras Maulina; Syamsul Mu’arif (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
This research aims to determine the influence of Institutional Ownership, Executive Characteristics, and Political Connections on Tax Avoidance. This study employs a quantitative research type, using secondary data. The research data sources were obtained from companies in the energy sector listed on the Indonesia Stock Exchange (IDX) over a five-year period between 2018 and 2022. The sampling method used in this research is purposive sampling, resulting in a sample of 11 companies obtained using this method. The data analysis technique used is panel data regression using E-views 12. The results of this research partially indicate that Institutional Ownership has a positive effect on Tax Avoidance, and Political Connections have a negative effect on Tax Avoidance. Meanwhile, the Executive Characteristics variable has no effect on tax avoidance. Simultaneously, Institutional Ownership, Executive Characteristics, and Political Connections have an effect on Tax Avoidance.